Synthesis of novel lower rim dimethylcarbamodithioate substituted calix[4]arene as selective and sensitive turn-on fluorescent sensor for detection of phosphate in aqueous solution. (11th May 2021) - Karimi, Nastaran; Zadmard, Reza; Parvizi, Parisa; Jalali, Mohammad Reza
Graphical abstract: Highlights: A novel lower rim dimethylcarbamodithioate substituted calix[4]arene (DT2 L) was synthesized. A highly selective and sensitive turn-on fluorescent sensor (DT2 L) for recognition of PO4 3− . The properties of the DT2 L-phosphate complex were proven by fluorescence and NMR titration methods with a LOD of 7.9 nM. Abstract: In this study, we synthesized a novel sensitive and selective dimethylcarbamodithioate substituted calix[4]arene sensor DT2 L for recognition PO4 3− among 20 various anions in CH3 CN/H2 O (99:1 v/v) solvent system. The structure of DT2 L was determined by HRMS, 1 HNMR, and 13 CNMR. The properties of DT2 L-phosphate complex were proven by fluorescence and NMR titration methods with a LOD of 7.9 nM, and binding constant 4 × 10 7 M −1 .